PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA POKOK BAHASAN PELUANG TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMP - Hamda, Agil (Departemen Matematika, 2023)
The purpose of this research is to make interactive learning media for mathematical problem solving ability of junior high school students in grade VIII on chance material. Plomp's development model, which consists of initial analysis, development, and assessment, was used in this study. The instruments used in this study were questionnaires, interviews, and tests, while the data analysis techniques used were descriptive statistics and descriptive techniques. Learner analysis, curriculum, concepts, and learner characteristics were studied during the initial analysis phase. Multimedia-based interactive learning media were created during the development phase and tested on learners in two evaluation stages: one-on-one and small group. During the assessment phase, the effect of using the learning media on learners' ability to solve mathematical problems was evaluated. The results showed that the intuitive learning media on the subject of probability has been declared valid, functional (practical), and effective (at the small collection stage). This media is considered valid because of its logical presentation, content, language, and graphics, as well as its development in accordance with the principles of scientific knowledge. It is also useful because it is easy to use and follows established rules. This media also utilizes time well, is interesting, and easy to understand. This learning media is also effective because it can help students in practicing their ability to solve math problems. Keywords– Interactive Learning Media Development, Multimedia, Probability, Mathematics Problem Solving Ability.